Elevated Air Humidity Changes Soil Bacterial Community Structure in the Silver Birch Stand - Truu, Marika; Ostonen, Ivika; Preem, Jens-Konrad; Lõhmus, Krista; Nõlvak, Hiie; Ligi, Teele; Rosenvald, Katrin; Parts, Kaarin; Kupper, Priit; Truu, Jaak (Frontiers in Microbiology, 2017)
Soil microbes play a fundamental role in forest ecosystems and respond rapidly to changes in the environment. Simultaneously with the temperature increase the climate change scenarios also predict an intensified hydrological cycle for the Baltic Sea runoff region. The aim of this study was to assess the effect of elevated air humidity on the top soil microbial community structure of a silver birch (Betula pendula Roth.) stand by using a free air humidity manipulation facility (FAHM). The bacterial community structures of bulk soil and birch rhizosphere were analyzed using high-throughput sequencing of bacteria-specific16S rRNA gene fragments and quantification of denitrification related genes. The increased air humidity altered both bulk soil and rhizosphere bacterial community structures, and changes in the bacterial communities initiated by elevated air humidity were related to modified soil abiotic and biotic variables. Network analysis revealed that variation in soil bacterial community structural units is explained by altered abiotic conditions such as increased pH value in bulk soil, while in rhizosphere the change in absorptive root morphology had a higher effect. Among root morphological traits, the absorptive root diameter was strongest related to the bacterial community structure. The changes in bacterial community structures under elevated air humidity are associated with shifts in C, N, and P turnover as well as mineral weathering processes in soil. Increased air humidity decreased the nir and nosZ gene abundance in the rhizosphere bacterial community. The potential contribution of the denitrification to the N2O emission was not affected by the elevated air humidity in birch stand soil. In addition, the study revealed a strong link between the bacterial community structure, abundance of denitrification related genes, and birch absorptive root morphology in the ecosystem system adaptation to elevated air humidity.